Time to light up the NBC airwaves - Ian Boden (Asia Pacific Network, 1995)
The NBC is a shadow of its former self. The provincial Kundu service, following years of neglect, has become an unproductive shambles. The flagship Karai service has a weak signal. And the 'cash cow' Kalang has contributed little.